About a right’s claim: the search for assurances towards the althusserian damage - Leite, Felipe Melonio (2021)
We look, in this paper, the reception of the althusserianism as bearer of a challenge to the social theory project’s, namely, the affirmation of the partial character of all possibility of unequivocal closure to the theoretical making. This damage was, certainly, thought provoking for authors of other theorical bases. We noticed, in the present elaboration, three paradigmatic responses that worked as a reaffirmation of a basilar point for their theoretical buildings. They were answers against elements, since the beginning, present in the althusserian critic: the theoretical anti-humanism, the anti-historicism and the normative anti-teleologism. We will analyze, for that matter, the approaches of Carlos Nelson Coutinho, E. P. Thompson and Ruy Fausto, exponents of each of the perspectives mentioned above.